Public Health Messages for Social Behavior Change in the Wake of COVID-19: A Qualitative Study - Al Araimi, Fannah Al Fannah (Oman Med J, 2021)
OBJECTIVES: We sought to study the impact of public health messages on social and behavioral change among recovered patients and the general population in response to coronavirus-2019 (COVID-19) in Oman. METHODS: Four focus group discussions among recovered COVID-19 patients were organized and conducted via video conference to collect their insights on public health messages. Upon culmination of each discussion, we held debrief sessions with a particular focus on the responses and making notes of comments. Qualitative themes were also recorded at the end of each focus group. RESULTS: All 40 participants were COVID-19 recovered cases. The participants' mean age was 33.4±28.5 years, and 70.0% (n = 28) were males. We observed a generally positive attitude towards public health messages. However, it was stressed that the nature of such behavioral change posed a significant risk for psychological health. Lack of social interaction, for example, led to lower motivation, a sense of losing the meaning of life, and personal distress. While all participants acknowledged and appreciated the government authorities' efforts in disseminating and educating the masses on such a large scale using different modes of message delivery, all showed a serious concern as to whether they will be able to continue coping with the ongoing situation. CONCLUSIONS: The participants' responses suggest that public health messaging brought a significant social change in Oman. However, this conclusion cannot be generalized. Further, there is a continued need for strong public health policies with a particular focus on psychological health.